2006
DOI: 10.2466/pms.102.2.543-551
|View full text |Cite
|
Sign up to set email alerts
|

Review of Three Tests of Motor Proficiency in Children

Abstract: The present purpose is to provide clinicians, occupational and physical therapists, and educators with a comparative analysis of three tests of motor proficiency. The Bruininks-Oseretsky Test of Motor Proficiency, Movement Assessment Battery for Children, and Tufts Assessment of Motor Performance were developed to assess the motor skills of children with developmental delays. The selection criteria, interrater reliability, reproducibility, and recommended use of each test are reported here. Recommendations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 23 publications
3
31
0
3
Order By: Relevance
“…The tasks are arranged from easy to difficult, so an individual's overall performance can be determined based on the difficulty of each task successfully performed. Even though the scoring is quite complex it appears useful for adolescents and adults with physical disabilities (Yoon et al, 2006), although there are no reported studies of its use with young adults with minor developmental impairments such as DCD. We have chosen to include this test at it assesses functional problems and activities of daily living which are not included in the other tests.…”
Section: Tufts Assessment Of Motor Performance (Tamp)mentioning
confidence: 99%
See 1 more Smart Citation
“…The tasks are arranged from easy to difficult, so an individual's overall performance can be determined based on the difficulty of each task successfully performed. Even though the scoring is quite complex it appears useful for adolescents and adults with physical disabilities (Yoon et al, 2006), although there are no reported studies of its use with young adults with minor developmental impairments such as DCD. We have chosen to include this test at it assesses functional problems and activities of daily living which are not included in the other tests.…”
Section: Tufts Assessment Of Motor Performance (Tamp)mentioning
confidence: 99%
“…Most tests of motor proficiency and impairment have been developed for children up to 12 years of age (Cools, De Martelaer, Samaey, & Andries, 2009;Slater, Hillier, & Civetta, 2010;Wiart & Darrah, 2001;Yoon, Scott, Hill, Levitt, & Lambert, 2006). Despite this, some have been used to assess motor performance in adolescents or adults.…”
Section: Introductionmentioning
confidence: 97%
“…The BOT-2 BF was selected for its suitability to assess children with and without motor problems and strong test-retest reliability (Yoon et al, 2006), as well as being a validated assessment instrument for motor proficiency for participants aged between 4-21 years of age (Bruininks & Oseretsky, 2010). The BOT-2 BF consisted of 12 measures of motor proficiency, which are categorized into sub-tests to assess fine motor precision, fine motor integration, manual dexterity, bilateral co-ordination, balance, speed and agility, upper-limb co-ordination and strength.…”
Section: Methodsmentioning
confidence: 99%
“…The Movement Assessment Battery for Children (MABC) (Henderson & Sugden, 1992) has been recognized as one of the most frequently used, comprehensive and valid instruments for assessment of a child's motor proficiency including identification of motor impairments (Yoon, Scott, Hill, Levitt, & Lambert, 2006). On the basis of larger changes of the content and structure of the 1 st older version of the MABC, a revised 2 nd version of this test battery -the Movement Assessment Battery for Children-2 (MABC-2) was created (Henderson, Sugden, & Barnett, 2007).…”
Section: Introductionmentioning
confidence: 99%